DETERMINATION OF THE SHELF LIFE AND EXPIRY DATE OF HERBAL COMPOUND DRUGS: A REVIEW - Dr. Mohd. Fazil, Dr. Sadia Nikhat (International Journal of Scientific Research and Management (IJSRM), 2013)
Herbal medicines are being used by nearly about 80% of the world’s population. With theadvancements in herbal drug treatments, it has now been observed that many of the constituents presentin the drug may react with each other, raising concerns about the stability of such formulations. Adetailed literature review of Unani classics and modern resources was made to find out what methods ofshelf-life determination may be suitable for Unani drugs; especially compound drugs, in the present era.Three methods, viz., activity-based standardization, determination of biologically active compound andstandardization of herbal drugs on various physical, chemical and other parameters were found to besuitable and practically applicable. These methods may be reproduced at various intervals to determinethe time when the drug loses its characteristic properties, i.e., its shelf-life